2015
DOI: 10.3124/segj.68.23
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic strain measurements using distributed sensor system under static pressure conditions

Abstract: 2014 9 26 * ( ( ) CO2 ) 690-8504 1060 ** 615-8540 C1 *3 ( ) CO2 619-0292 9-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…This was obtained from calibration using a tensile tester with a displacement gauge. A standard metal plate with an optical fiber bonded (by an epoxy adhesive) was stretched under a strain-controlled condition (Kogure et al, 2015). These conditions matched those of the strain measurements during the current core test.…”
Section: /2019wr024795mentioning
confidence: 96%
See 1 more Smart Citation
“…This was obtained from calibration using a tensile tester with a displacement gauge. A standard metal plate with an optical fiber bonded (by an epoxy adhesive) was stretched under a strain-controlled condition (Kogure et al, 2015). These conditions matched those of the strain measurements during the current core test.…”
Section: /2019wr024795mentioning
confidence: 96%
“…Water Resources Research guarantee tight bonding. The same installation has been deployed in prior experimental investigations, which showed that DFOSS has similar or better performance compared to conventional strain gauges (Kogure et al, 2015;Xue et al, 2018). Because the fiber was much smaller than a usual strain gauge, the contact problem was less significant.…”
Section: Rock Sample and Experimental Setupmentioning
confidence: 99%
“…In order to make accurate predictions, a geomechanical model needs to be first calibrated against geophysical and geomechanical data obtained from monitoring. As a new technology, continuous and distributed fiber optic sensing (DFOS) technology based on Brillouin and/or Rayleigh scattering has great potential in geotechnical monitoring at both laboratory and field scales [16][17][18][19][20]. Optical fiber sensors have advantages such as their immunity against electromagnetic interference, low weight, small size, high sensitivity, and large bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that Rayleigh-based sensing has a much higher resolution than Brillouin-based sensing does. Rayleigh and Brillouin backscattering techniques have been successfully applied in measuring metallic plate strains [14]. In this study, they are applied to measure frequency shift along the interval of a single optical fiber which is attached to and circles around the peripheral of two different sandstone cylindrical core samples under controlled confining/pore pressure conditions in the laboratory.…”
Section: Introductionmentioning
confidence: 99%